Thermal properties of high-entropy RE-disilicates controlled by high throughput composition design and optimization - Wang, Yuhan; Zhu, Jinpeng; Li, Mingliang; Shao, Gang; Wang, Hailong; Zhang, Rui (Materials & design, 2023)
The configuration entropy was manipulated by introducing atoms with unique properties using the high throughput calculations, and five new disilicates with ideal properties which have lower thermal conductivity and controllable thermal expansion coefficient were obtained through composition design. From a microstructural perspective, the inclusion of atoms with larger ionic radius differences (reaching a 4.11 % contrast with Yb2Si2O7) can cause sever lattice shrinkage (9.49 % compared to single-component disilicates), which leads to lower thermal conductivity and a change in the thermal expansion coefficient. At 1200 °C, the thermal expansion coefficient of the five high-entropy disilicates ranged from 4.57 × 10-6 K−1 to 4.84 × 10-6 K−1, and the minimum thermal conductivity was only 1.14 W/m·K. Additionally, the local charge disorder facilitates the transfer of electrons around Si-O to Sc, which reduces the covalent bond strength of Si-O and regulates the thermal expansion coefficient. This phenomenon has been proved in the five non-equimolar high-entropy disilicates with different contents of Sc, effectively regulating the thermal expansion coefficient in 4.08 × 10-6 K−1 to 5.04 × 10-6 K−1. This study presents a novel method for controlling the thermal properties of disilicates and expands the possibilities for selecting thermal protective coating materials for ultra-high temperature SiC-based ceramic composites.